The Influence of Parenting Style on College Students' Interpersonal Communication Skills - Sun, Bo (Transactions on Social Science, Education and Humanities Research, 2024)
College students' interpersonal communication skills are needed for society's development. That is because interpersonal communication skills can access information, show off themselves, and promote personal growth. In China, there are many researchers who have researched the influence of parenting style on college students' specialty, personality, and so on. However, there is little research on the effect of parenting style on college student's interpersonal communication skills. To fill some gaps in this area, this study has used an investigation through a questionnaire of college students to research the influence of parenting style on college students' interpersonal communication skills. This study has found that the fathers' parenting style has a positive impact on college students' interpersonal communication skills, the mothers' parenting style has a positive influence on college students' interpersonal communication skills, and differences in the influence of parenting styles of fathers and mothers on college students' interpersonal communication skills. From this research, what should parents do to improve interpersonal communication skills among college students? What is the current situation of interpersonal communication skills among college students? From this research, it can be known that suitable parenting styles can improve good interpersonal communication skills, which can help college students get more helpful information to better survive in society. Therefore, if college students want to develop nicely in society, parenting style really plays an important role.